THE FUTURE OF MOBILE MARKETING – INTELLIGENT CONNECTIVITY IN MOBILE MARKETING COMMUNICATION EFFORTS. - Aho, Jarkko (My University, 2022)
In the Spring of 2019, during the MWC (formerly known as the Mobile World Con-gress), GSM Association’s Director General Mats Granryd publicly discussed intelligent connectivity for the first time. Intelligent Connectivity enables applications to be smarter, making life better and safer. The effects of intelligent connectivity on mobile marketing communication is still to materialize. This study was conducted to provide a view in to the future to the possibilities that come with the introduction of the intelligent connectivity to the mobile marketing communication This study was conducted as a qualitative research, which data comprised of four themed interviews of the personnel working for the company X. The people were chosen because of their expertise with either intelligent connectivity’s elements, mobile marketing communication, or both. Intelligent connectivity consists of 5g, internet of things, big data, and artificial intelligence. Each key element of the intelligent connectivity will work and advance in symbiosis with the other. Intelligent connectivity will provide new channels as well as the introduction of the artifi cial intelligence handling mobile marketing communication. There are also threats in the future for the intelligent connectivity. Intelligent connectivity will change the requirements of how the company X will operate. There needs to be new KPIs in place and also the corporate culture should encourage the trials of new innovative solutions in mobile marketing communication.
Keywords: Intelligent connectivity, 5g, Internet of things, big data, artificial intelligence, Mobile marketing communication